Middle East Respiratory Syndrome - Rampengan, Novie H. (Jurnal Biomedik : JBM, 2016)
Abstract: Middle East Respiratory Syndrome (MERS) is a respiratory disease caused by Corona virus (MERS-CoV). This virus was first reported in 2012 in Saudi Arabia. World Health Organization (WHO) reported that until June 2015 there were 26 countries infected by MERS-CoV with a total of 1,334 laboratory confirmed cases of MERS-CoV infection and 471 deaths. According to WHO as many as 75% of MERS-CoV cases are secondary cases, obtained from other infected people. In mid 2015 it is reported that MERS-CoV attacked South Korea with 172 confirmed cases of MERS-CoV and 27 deaths. There are no approved antiviral agents for the treatment of MERS-CoV infection or vaccine available for the prevention of MERS-CoV. MERS cases are treated with supportive therapy such as hydration, antipyretics, analgesics, respiratory support, and antibiotics in case of secondary infectionKeywords: Middle East Respiratory Syndrome, Corona virus, treatmentAbstrak: Middle East Respiratory Syndrome (MERS) merupakan penyakit saluran napas yang disebabkan oleh Corona virus (MERS-CoV). Virus ini pertama kali dilaporkan pada tahun 2012 di Arab Saudi. WHO melaporkan bahwa sampai Juni 2015 terdapat 26 negara terinfeksi MERS-CoV dengan total 1.334 kasus yang dikonfirmasi laboratorium terinfeksi MERS-CoV dan 471 kematian. Menurut WHO sebanyak 75% dari kasus MERS-CoV merupakan kasus sekunder, yaitu diperoleh dari orang lain yang terinfeksi. Pada pertengahan tahun 2015 dilaporkan MERS-CoV menyerang Korea Selatan dengan 172 kasus yang dikonfirmasi laboratorium terinfeksi MERS-CoV dan 27 kematian. Belum ada antivirus yang disetujui untuk pengobatan infeksi MERS-CoV atau vaksin yang tersedia untuk pencegahan MERS-CoV. Penanganan MERS-CoV dengan terapi suportif berupa hidrasi, antipiretik, analgetik, bantuan pernapasan, dan antibiotik bila terjadi infeksi sekunder.Kata kunci: Middle East Respiratory Syndrome, Corona virus, penanganan